Characteristics of land tenancy on family farms in Vojvodina - Petrović, Živojin; Janković, Dejan (Economics of Agriculture, 2010)
Authors show the significance of land tenancy in the conditions of small and fragmented land property of family farms. The analysis was conducted on 1. 513 selected family farms that take land on lease and cooperate with Agricultural extension service of Vojvodina on issues of agricultural production improvement. The authors explore how much land is being taken on lease, what is the relation between owned agricultural land and land on lease, what are the reasons for the taking land on lease, do the owners of the selected family farms have intentions to buy land and for what reasons. Also, the paper gives a review of some basic information on socio-economic characteristics of families that take land on lease.